Analisis Penerapan Akuntansi Pertanggungjawaban - Habiburrahman, Habiburrahman; Zanaria, Yulita; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze the implementation of responsibility accounting at RSU Muhammadiyah Metro. Responsibility accounting is an accounting system that recognizes various responsibility centers within an organization, assigning specific revenues and costs to each responsible center. This research uses primary and secondary data collected through observation, interviews, and documentation. The results of the research show that RSU Muhammadiyah Metro has implemented responsibility accounting well, characterized by the existence of a clear organizational structure, budget preparation, separation of controlled and uncontrolled costs, and account code classification. Financial performance evaluation shows that the RSU Muhammadiyah Metro cost center is efficient in 2020 but inefficient in 2021. Meanwhile, the revenue center shows efficiency from 2020 to 2021 with profitable results. The advice given is that RSU Muhammadiyah Metro needs to carry out analysis and correction of unprofitable differences so that it can increase the effectiveness of cost management and encourage the success of hospital operations